LABORATORY HYDRATION OF CONDENSED MAGNESIOSILICA SMOKES WITH IMPLICATIONS FOR HYDRATED SILICATES IN IDPS AND COMETS - Rietmeijer F.J.M.; Nuth III J.A.; Nelson R.N. (My University, 2004)
Samples of silica-rich and MgO-rich condensed, amorphous magnesiosilica smokes were hydrated to monitor systematic mineralogical and chemical changes as a function of time and temperature controlled by their unique metastable eutectic compositions, their porous texture, and the ultrafine, nanometer grain size of all entities. At water supersaturated conditions, proto-phyllosilicates formed by spinodal-type homogeneous nucleation. Their formation and subsequent growth was entirely determined by the availability of water via pore spaces inherited from the original smokes and the textural continuity of magnesiosilica material with a mostly smectite-dehydroxylate composition. The results may have implications for the hydration of proto-CI material, the presence of rare periclase and brucite in primitive solar system bodies, and the pervasiveness of hydrated amorphous magnesiosilica dust and saponite proto-phyllosilicates in icy-protoplanets, such as comet nuclei.